More than just crushing: a prospective pre-post intervention study to reduce drug preparation errors in patients with feeding tubes - Lohmann, Kristina; Gartner, D.; Kurze, R.; Schösler, T.; Schwald, Martina; Störzinger, Dominic; Hoppe-Tichy, Torsten; Haefeli, Walter E.; Seidling, Hanna (Journal of clinical pharmacy and therapeutics, 2015)
What is known and objectives Incorrect drug preparation for patients with feeding tubes can result in harm for the patient and the preparing person. Combined intervention programs are effective tools to reduce such preparation errors. However, to date, intervention programs have been mostly tested in hospitals with computerized physician order entry (CPOE), unit-dose systems, or ward-based clinical pharmacists. Hence, the primary objective of this study was to develop and evaluate an intervention program tailored to hospitals without such preconditions. Methods We conducted a prospective pre-/post-intervention study on a gastroenterological intensive care unit (ICU) and a surgical ward for oral, dental and maxillofacial diseases (surgical ward). During the study periods, observers documented and evaluated drug preparation processes of all peroral drugs for patients with feeding tubes. The primary endpoint was the rate of inappropriately crushed and/or suspended solid peroral drugs in regards to all solid peroral drugs. Results and discussion Altogether, we evaluated 775 drug preparation processes of solid peroral drugs on the ICU and 975 on the surgical ward. The intervention program significantly reduced incorrect crushing and/or suspending of solid peroral drugs for administration to patients with feeding tubes from 9·8% to 4·2% (P < 0·01) on the ICU and from 5·7% to 1·4% (P < 0·01) on the surgical ward. What is new and conclusion The implementation of the newly developed intervention program significantly reduced the rate of inappropriately prepared solid peroral drugs, suggesting that it is an effective measure to enable safe drug administration for inpatients with feeding tubes.